Artists in the Archive: An Exploratory Study of the Artist-in-Residence Program at the City of Portland Archives & Records Center - Carbone, Kathy (Archivaria, 2015)
Reporting on components of an exploratory study (2013–14) of the inaugural artist-in-residence program at the City of Portland Archives & Records Center in Oregon, this article provides a view of the experiences and actions of the archivists, the artists, and the public arts manager participating in the residency. It pays particular attention to how the artists conceptualize, use, and respond to archival records, how and where the records circulate as works of art and poetry, and how connections are formed around the use and reuse of records. The study suggests that examining the records used in such a residency from the standpoints of their forms, uses, and paths through space and time is a productive way to reflect on the human transactions, experiences, and relationships that can occur between records, art, poetry, and the archive. RÉSUMÉ En faisant le point sur des parties constituantes d’une étude exploratoire (2013-2014) sur le programme inaugural d’artiste en résidence au City of Portland Archives & Records Center, en Oregon, ce texte présente un aperçu des expériences et des actions des archivistes, des artistes et de l’administrateur des arts publics qui ont participé au programme. Ce texte porte une attention particulière aux façons dont les artistes conceptualisent les documents d’archives, comment ils s’en servent, comment ils y réagissent. Il se penche aussi sur les raisons pour lesquelles les documents d’archives circulent comme oeuvres d’art et poésie, et les lieux où ils circulent, ainsi que les liens qui sont forgés entre l’utilisation et la réutilisation des documents d’archives. Cette étude suggère que l’examen des documents d’archives dont se sont servis les artistes en résidence, du point de vue de leur forme, de leur utilisation et de leur trajet à travers le temps et l’espace, constitue une façon enrichissante de penser aux transactions, aux expériences et aux relations humaines qui peuvent se produire entre les documents d’archives, l’art, la poésie et les archives.